Green magnetite nanocomposite sheet using coprecipitation loading method as a wave absorber in RFID applications - Mustaq Ahmad, Mohd Khairul Sharil (2014)
EM wave absorber had been used to solve the RFID interference problem when it is used in near metallic environment. Synthetic polymeric matrix from various cellulosic pulps were used to produce wave absorbers with magnetite as its main reinforcement using two different approaches namely lumen loading method and in-situ coprecipitation method. Since both methods were a successful in terms of green technology and cost reduction, this study focused on enhancing the previous two methods by introducing a new developed method called as coprecipitation loading method. Besides that, the exploration of the compatibility of paddy straw and recycled paper as the magnetic sheet matrix also was done to add the green technology value. Result obtained reveal that paddy straw and recycled paper are very good candidate to be embedded with nano-magnetite particles thus conforming its compatibility to be used as a substrate to produce the wave absorber. All three loading methods have good degree of loading around 18.4% to 34.4%, and VSM data also shows that the magnetic wave absorbers exhibit good superparamagnetic behaviour. The proposed method consume less power to be produced compared to the previous methods thus contributes to green environmental effects. All samples were tested in the HF RFID application near to metallic environment showing great performance in alleviating the interference problem and recover up to 60% of the distance detection by comparing to the commercial wave absorber. By using the loading methods and substrates proposed, this research contributes to the production of Green Magnetite Nanocomposites Sheets using substrate from paddy straw and recycled paper pulp combined with magnetite nanoparticles. Besides that, the introduction of coprecipitation loading method also enables magnetic sheet to be produced using less energy compared to previous methods. Lastly, samples produced indicate that the green magnetic wave absorber do perform its main purpose in the RFID application near metallic environment.